(untitled) (Jurnal Geomine, 2015)
Acid mine drainage to get potentially contaminate artless waters body if uncommitted management which well so to the effect of observational it which is know water handle stage acid at pit’s area and water processing acid mine at settling pond. Method that is utilized in this research which is by undertaking measures pH water at pit’s area and settling pond, measuring nfalted water at channel inlet and outlet, and accounting bigger water amount bases rainfall. Water management mines at Pit 1 PT. Rimau Energy Mining did by process dewatering, base observational result to be gotten runoff ingoing goes to sump pit is 8.05 m3/second. Water those are on sump pit then at outward pump from pit by use of mitsubishi’s type pump 6D15 with pumps maximum capacity which is 639 m3/day. Inflated water then is streamed making for settling pond via channel with channel capacity 0.416 m3/second. The total volume of water storage settling pond as big as 14270 m3 so needed time particle to precipitate which is 9519 hours. Base evaluation result to sediment stability was gotten by that conclusion settling pond existing safe to scouring with parameter doesn’t exceed to stipulate Reynold’s number which is Re <2000 and Froude number is Fr<0.005. Water processing acid mine is done by use of active processing method which is whitewash and alum application with rapid mixing that its mixing energy comes from hydraulic waterfall.